2020
DOI: 10.1177/0033354920915439
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Good Samaritan Laws and Beliefs About Arrests Among Persons Who Inject Drugs a Year After Policy Change in Baltimore, Maryland

Abstract: Objectives Delivering and receiving prompt medical care during an overdose are imperative to ensure survival. Good Samaritan laws encourage people to call 911 during an overdose by providing immunity from selected drug arrests (eg, low-level possession). However, it is unclear whether persons who inject drugs (PWID) are aware of and understand these laws and their implications. We examined awareness among PWID of the 2015 Good Samaritan law in Maryland and their beliefs about whether they could be arrested for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 30 publications
4
28
0
Order By: Relevance
“…Beyond awareness, our ndings demonstrate that many people do not have an accurate understanding of the GSDOA and the legal protections it provides. These ndings are comparable to results from two US studies and two studies conducted in BC [24,26,29,63]. Notably, a study from BC found that only 45% and 61% of respondents who were aware of the GSDOA had a complete understanding of when and to whom protection was offered, respectively [26].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Beyond awareness, our ndings demonstrate that many people do not have an accurate understanding of the GSDOA and the legal protections it provides. These ndings are comparable to results from two US studies and two studies conducted in BC [24,26,29,63]. Notably, a study from BC found that only 45% and 61% of respondents who were aware of the GSDOA had a complete understanding of when and to whom protection was offered, respectively [26].…”
Section: Discussionsupporting
confidence: 80%
“…To our knowledge, the majority of studies evaluating the GSDOA/drug-related Good Samaritan Laws use quantitative methods [16,[20][21][22][23][24][25][26][27][28][29][30], with, to our knowledge, only two multi-or mixed-methods studies [31,32]. Different methodologies may in uence the ndings that are produced.…”
Section: Introductionmentioning
confidence: 99%
“…We found greater GSDOA awareness among respondents who reported more frequent access to harm reduction services. A study conducted in Maryland, in the United States, demonstrated that individuals who accessed syringe service programs were more likely to have accurate knowledge of the drug-related GSL (Schneider et al, 2020). Also, similar to a study by Evans at al.…”
Section: Discussionmentioning
confidence: 56%
“…A study conducted in the state of Rhode Island explored factors associated with drug-related GSL awareness among young adults engaged in non-medical prescription opioid (NMPO) use and found that 45.5% of respondents were aware of the law (Evans et al, 2016). While factors associated with drug-related GSL awareness in the United States have previously been reported, to our knowledge this study is the first in Canada to conduct a quantitative assessment to assess correlates of GSDOA awareness with a comprehensive sample of PWUD across BC (Evans et al, 2016;Schneider et al, 2020).…”
Section: Discussionmentioning
confidence: 92%
“…One study found that after states enact a GSL, they have 15% reductions in opioid overdose deaths (McClellan et al,2018). Other studies demonstrate that people who use drugs are unaware of their state's GSLs and their associated protections (e.g., Fadanelli et al,2020;Schneider et al,2020).…”
Section: Introductionmentioning
confidence: 99%